Psychometric evaluation of the Clinical Interview for Externalizing Disorders (ILF-EXTERNAL) in an online setting – Results from the consortium project INTEGRATE-ADHD - Sophia Weyrich; Vanessa Scholz; Leila Hetzke; Sanna Ulsamer; Chantal Wallau; Diana Mager; Julia Geißler; Marcel Romanos; Ann-Kristin Beyer; Robert Schlack; Anne Kaman; Ulrike Ravens-Sieberer; et al. (Journal of Health Monitoring, 2024)
Background: The study examines the psychometric properties of the ADHD section of the semi-structured diagnostic interview ILF-EXTERNAL, which was conducted online via video chat. Methods: As part of the INTEGRATE-ADHD research project, 202 children and adolescents (age M = 12.87 years, SD = 3.04, 28.2 % female) with an administrative diagnosis of ADHD registered with their health insurance company were clinically assessed for the presence of ADHD according to the German ADHD S3 guideline. Using the ILF-EXTERNAL, one parent and, from the age of eight, also the children themselves were interviewed. A proxy rating by a parent was made using the German FBB-ADHS rating scale. In a subsample (n = 65), an independent blind interviewer rated the videorecordings of the ILF-EXTERNAL parent interview to determine the interrater reliability of the ILF-EXTERNAL. Results: All ADHD symptom scales of the ILF-EXTERNAL showed good to excellent internal consistency (α = 0.89 to 0.93). Interrater reliability was high for both categorical and dimensional analyses (κ = 0.78 and κ = 0.81; ICC(1,1) = 0.97 and 0.98). High correlations of the ILF-EXTERNAL parent interview with the FBB-ADHS (r = 0.79 to r = 0.85) and with the ILF-EXTERNAL child interview (r = 0.60 to r = 0.71) demonstrated convergent validity. Conclusions: Sound psychometric properties of the ILF-EXTERNAL were also confirmed for its use in an online setting. High interrater reliabilities demonstrate the quality of the ADHD diagnostics carried out in the consortium project INTEGRATE-ADHD.